2017
DOI: 10.3390/w9120931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using High-Density Rain Gauge Networks and Weather Radar Data on Urban Hydrological Analyses

Abstract: Flood prediction is difficult in urban areas because only sparse gauge data and radar data of low accuracy are usually used to analyze flooding and inundation. Sub-basins of urban areas are extremely small, so rainfall data of high spatial resolution are required for analyzing complex drainage systems with high spatial variability. This study aimed to produce three types of quantitative precipitation estimation (QPE) products using rainfall data that was derived from 190 gauges, including the new high-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…On a daily scale, Burcea et al (2012) [35] also found that meteorological radar in the Moldavian Plaeau underestimated rainfall recorded by rain gauges. Changing the time scale from daily to ten minutes, similar results have also been documented in Seoul (South Corea) [39].…”
Section: Discussionsupporting
confidence: 76%
“…On a daily scale, Burcea et al (2012) [35] also found that meteorological radar in the Moldavian Plaeau underestimated rainfall recorded by rain gauges. Changing the time scale from daily to ten minutes, similar results have also been documented in Seoul (South Corea) [39].…”
Section: Discussionsupporting
confidence: 76%
“…Seoul is one of the most highly urbanized cities in South Korea with several residential areas and industrial facilities located near flood plains that are at risk from damage caused by urban flooding. Several researchers, and even the South Korean government, have worked to develop flood forecasting systems and methodologies for urban flood disaster mitigation [22][23][24]. Moreover, many kinds of QPF data are issued for the Seoul metropolitan area by the KMA, allowing us to easily evaluate the hydrological applicability and accuracy of various QPFs.…”
Section: Study Areamentioning
confidence: 99%
“…Rain gauges provide close to ground-truth precipitation observations, but very few networks with >50 gauges, densities of >0.1 gauges/1 km 2 , and subhourly recordings required to study convective area precipitation exist around the globe (e.g., Moore et al, 2000;Singer & Michaelides, 2017;Yoon & Lee, 2017). The very high density, long-term climate station network WegenerNet Feldbach Region (WEGN) in southeastern Austria provides a unique setting with 150 gauges (density 0.5 gauges/1 km 2 ).…”
Section: Introductionmentioning
confidence: 99%